Kajian Aksiologi Bahasa Indonesia sebagai Nilai dan Identitas Bangsa dalam Perspektif Filsafat Ilmu - Dewi Wahyu Utami; Fernanda Dafittra; Wahyu Mardaning Hardiyanti; Audrey Zhafira Salma; Sarwiji Suwandi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine the axiological values ​​in the Indonesian language, the function of Indonesian as a national identity, and the axiological function of language in the life of the nation and state. This study uses a qualitative method with a descriptive-analytical approach through a literature review of various literatures. The data collection technique uses a literature review (library research). The data sources of this study come from books on the philosophy of science, scientific articles indexed by Sinta, and national journals relevant to the theme of language, values, and national identity. Data analysis is carried out through several stages, including collecting relevant literature, the process of coding texts containing social, cultural, and moral values, then categorizing themes according to the types of values ​​found, followed by philosophical interpretation, and ending with drawing conclusions regarding the position of the Indonesian language as an axiological entity. The results of the study indicate that the Indonesian language has three main dimensions of value, namely social values, cultural values, and moral values. The social value of the Indonesian language is evident through its role in building togetherness, equality, and unity. Its cultural values ​​are manifested in the preservation of local wisdom, cultural richness, and diversity, while its moral values ​​are reflected through the use of polite, honest, and ethical language. Furthermore, Indonesian serves as a medium for education, the development of knowledge, and the expression of national ideology, affirming national identity.